Hello this question is based on a transfer function problem and I have the following formulas and need to arrive at an equation for T/VD in terms of k0, k1, k2 and kt
where E = VD - VM, I = Ek1, T = k0I, Vt = ktT and Vm = k2Vt
T = k0I where I = Ek1 therefore T = k0Ek1 where E = VD - VM hence T = K0(VD - VM)K1
Also we know that T = Vt/kt where Vt = VM/k2 therefore T = VM/(k2kt) hence VM = Tk2kt
and substituting VM = Tk2kt into T = K0(VD - VM)K1
we have T = K0(VD - Tk2kt)K1 expanding brackets: T = K0K1VD - K0k1Tk2kt
I've tried various rearragements of this but don't seem to come up with T/VD can anyone show me where I'm going wrong?
I'm really stuck